2017
DOI: 10.14814/phy2.13169
|View full text |Cite
|
Sign up to set email alerts
|

CLIC1 null mice demonstrate a role for CLIC1 in macrophage superoxide production and tissue injury

Abstract: We generated and studied CLIC1 null (C1KO) mice to investigate the physiological role of this protein. C1KO and matched wild‐type (WT) mice were studied in two models of acute toxic tissue injury. CLIC1 expression is upregulated following acute injury of WT kidney and pancreas and is absent in C1KOs. Acute tissue injury is attenuated in the C1KOs and this correlates with an absence of the rise in tissue reactive oxygen species (ROS) that is seen in WT mice. Infiltration of injured tissue by inflammatory cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…CLIC1 affects the innate arm of the immune system. It is highly expressed in macrophages and modulates the phagosomal proteolytic activity of macrophages via ROS generation (Jiang et al., ; Ulmasov et al., ). Furthermore, upon interaction with heat‐inactivated Candida albicans cells, RAW 264.7 macrophages show a decrease in expression of CLIC1 (Martinez‐Solano, Reales‐Calderon, Nombela, Molero, & Gil, ) as well as suppressed TNF‐α levels.…”
Section: Physiological Roles Of Clicsmentioning
confidence: 99%
See 1 more Smart Citation
“…CLIC1 affects the innate arm of the immune system. It is highly expressed in macrophages and modulates the phagosomal proteolytic activity of macrophages via ROS generation (Jiang et al., ; Ulmasov et al., ). Furthermore, upon interaction with heat‐inactivated Candida albicans cells, RAW 264.7 macrophages show a decrease in expression of CLIC1 (Martinez‐Solano, Reales‐Calderon, Nombela, Molero, & Gil, ) as well as suppressed TNF‐α levels.…”
Section: Physiological Roles Of Clicsmentioning
confidence: 99%
“…CLICs belong to the family of intracellular ion channels that includes the mitochondrial large‐conductance Ca 2+ ‐activated K + channel (mitoBK Ca ), mitochondrial ATP‐dependent K + channel (mitoK ATP ), voltage‐dependent anion channel (VDAC), mitochondrial calcium uniporter (MCU), ryanodine receptor (RyR), and inositol triphosphate receptor (IP3R; Kiselyov & Muallem, ; Leanza et al., ; O'Rourke, ; Singh et al., ). There are six mammalian CLIC paralogs and, under physiological conditions, the majority of the CLICs are present on intracellular organelles and in the cytoplasm (Singh, ; Ulmasov et al., ). In addition to intracellular organelle membranes, CLICs can associate with the plasma membrane (Averaimo, Milton, Duchen, & Mazzanti, ; Milton et al., ; Tang et al., ; Warton et al., ) under pathological conditions or upon overexpression.…”
Section: Localization Of Clicsmentioning
confidence: 99%
“…Given its presence as a soluble protein in the cytosol, phylogenetic prediction suggests that CLIC1 may have enzymatic function ( Littler et al, 2010 ), and soluble CLIC1 displays glutathione-dependent oxidoreductase activity in a cell-free system ( Al Khamici et al, 2015 ). Clic1 knockout mice were viable and fertile and appeared normal, aside from showing a mild defect in platelets and macrophages ( Qiu et al, 2010 ; Ulmasov et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is an active element that contributes to the condition of oxidative stress in the cell [12][13][14], has functional connection with the cytoskeleton [15][16][17], and once in the membrane, it controls chloride flux through the lipid bilayer [10,11,19]. All these functions are linked to cell proliferation, cell migration and infiltration [11,13,[15][16][17]19]. We focused on monocytes because they are the ideal elements to investigate CLIC1 properties.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the transmembrane form, CLIC1 is associated with chloride ions' permeability [10,11]. Recent investigation demonstrated that tmCLIC1 and NADPH oxidase are involved in a feed-forward mechanism that increases the production of reactive oxygen species (ROS) [12], particularly in macrophages [13]. This is instrumental in speeding up the transition G1/S phase during the cell cycle [14].…”
Section: Introductionmentioning
confidence: 99%